Perubahan Penggunaan Lahan di Kota Medan Tahun 2014/2024 - Renintan, Eliana; Aminarti, Rini; Matondang, Muhammad Farouq Ghazali; Zulfajri, Zulfajri (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This study aims to analyze land use changes in Medan City during the period 2014–2024 by utilizing Landsat 8 satellite imagery and a Geographic Information System (GIS) approach. The analysis was conducted through image interpretation and calculation of the area of each land use class. The results indicate an increase in residential land area of +40.56 hectares, reflecting the expansion of housing areas driven by population growth and increasing demand for urban infrastructure. In contrast, there were decreases in industrial land (–11.97 hectares), plantation land (–62.25 hectares), water bodies (–63.37 hectares), and agricultural land (–15.30 hectares). These declines indicate an intensive land use conversion from the primary sector to the secondary and tertiary sectors. This phenomenon also illustrates a rapid urbanization pattern, in which productive land is reduced due to the development of residential areas and infrastructure. Therefore, the findings of this study emphasize the need for sustainable urban spatial planning to ensure that land use changes do not negatively affect ecological balance and the urban environment.